KARAKTERISTIK, MOTIVASI DAN AKTIVITAS WISATAWAN ASIA DI KELURAHAN UBUD - Christine Pratama, Axel; Sasrawan Mananda, I GPB; Sudarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 4 No 1 (2016): Jurnal IPTA (July 2016), 2016)
The types of the data that are used in this research are primary and secondary data. All the datas are collected through an observation method, questionnaires, literature study and documentation. The sample is collected by non-random sampling method. Analysis technique that is used in this research is qualitative descriptive analysis. This research result showed that the Asia tourists who came to Ubud for the first time are 96 tourists and the repeater tourists are 9 (nine) people. The characteristic of the tourists according to the age who came to Ubud the most is tourists between 26-36 years old and most of the gender are male. Most of the tourists are from China. According to the occupation, most of the tourists are student with bachelor degree, they got the information about Ubud from their friends and they came to Ubud with groups. Most of them are the first timer visitors and they came by car or bus and came to Bali by airplane. Mode of transportation which is used when the tourists are in Ubud mostly is rented vehicles and stay in Ubud for a day without the tour. The attraction they want to see in Ubud is the culture with the expenses around Rp 201.000-300.000 in a day. According to the tourists who came to Ubud, Ubud’s environment is very clean and safe, so they feel very satisfied and they definitely will come back again to Ubud. The motivation of the tourists who came to Ubud the most is the tourists with the pleasure motivation and the main activity they want to do is to visit Ubud market.
Keywords: Characteristic, Motivation, Activity, Asian Tourists